Meningkatkan Efektivitas Penanganan Gangguan Jaringan Internet Menggunakan Bot Telegram Dalam Mendukung Reliabilitas Komunikasi Data - Zainal Arifin (Jurnal Algoritma, 2023)
Fast and effective handling of internet network disturbances is very important in maintaining the quality of internet services. This study aims to increase the effectiveness of handling internet network disturbances using the Telegram Bot as a supporting tool in repairing internet network disturbances. This research involves internet subscribers who have experienced disturbances and internet network technicians who are responsible for handling these disturbances. The research method used is experimental by using the Telegram Bot as a supporting tool. The results of the study show that the use of the Telegram Bot can increase the effectiveness of handling internet network disturbances by providing real-time disturbance messages to the technicians who are responsible for handling disturbances for follow-up. Therefore, the use of Telegram Bot can increase the reliability of data communication in handling internet network disturbances and speed up the recovery time for internet networks that are experiencing disruptions.